Analisis Faktor–Faktor yang Mempengaruhi Kerentanan Kemiskinan Relatif di Kota Jakarta Barat Tahun 2018 - Mokhamad Fuad Fadilah; Maruto Umar Basuki (Diponegoro Journal of Economics, 2020)
West Jakarta district is one of the municipalities in DKI Jakarta Province still has problem regarding in relative poverty. As well as identifying poverty profiles, measuring the vulnerability is also a key for reducing poverty. This study focused on measuring vulnerability to relative poverty in West Jakarta District. The measurement of vulnerability to poverty in this study based on the probability of households becoming relatively poor. This research used binary logistic regression model. The type of data used is secondary data obtained from the National Social Economic Survey (SUSENAS) in March 2018 in West Jakarta district with 982 households as a total sample. The dependent variable in this study is the status of poor households relative in West Jakarta District. There are 4 independent variables in this research, the independent variable is the age of the head of the household, the education of the head of the household, the number of family dependents and the status of home ownership. This research found that 4 independent variables which is age of the head of the household (negative correlation), the education of the head of the household (negative correlation), the number of household dependents (positive correlation) and the status of home ownership (negative correlation) significantly influence the relative poverty of the household in West Jakarta district. Increasing educational assistance such as the distribution of the ‘Kartu Jakarta Mahasiswa Unggul (KJMU)’, emphasizing the number of children and access to affordable housing can be number of options to overcome the problem of relative poverty in West Jakarta district.